Description of the development of village-owned enterprises in Pahae Jae sub-district, North Tapanuli district, North Sumatra Province - Mangasa Sinurat; Hamonangan Siallagan; Bonifasius H. Tambunan; Febryen Mauli Sinaga (Institute of Computer Science (IOCS), 2023)
The government of the Unitary State of the Republic of Indonesia, starting from the central government to the village government, continues to strive and is committed to improving the economic welfare of its people. One tangible manifestation is the encouragement of a village to establish a Village-Owned Enterprise (BUMDes), whose initial capital can be sourced from the Village Fund. In addition, the government has also issued legal regulations that will protect BUMDes operations, as well as the participation of the district government to conduct technical guidance through officials of the Village Community Empowerment Office. However, over time in the management of BUMDes, there are several research results that reveal that BUMDes have developed rapidly. However, on the contrary, there are also BUMDes that have been established but are no longer active. In addition, from the results of the BUMDes performance assessment, most of them are still in the basic, growing, and developing classifications. The purpose of this research was conducted to describe the business development of BUMDes in Pahae Jae Sub- district, North Tapanuli Regency, North Sumatra Province. The types of data used in this research are primary and secondary data. Primary data in the form of answers from Operational Executives. The primary data collection method is to submit questionnaires and questionnaires. While secondary data in the form of local government policies and data from the Central Bureau of Statistics of North Tapanuli Regency in 2022. The secondary data collection method is documentation. From the results of data analysis in this study, the following conclusions can be made; from the legal aspect, BUMDes is still not in the form of a Legal Entity, and the Operational Executive has not fully guided the BUMDes regulations. From the management aspect, the inhibiting factors are the lack of HR skills, the lack of inadequate work coordination. While from the accounting aspect that; have not made complete transaction records, and do not understand the preparation of SAK-EMKM-based financial statements. Overall, the performance of BUMDes in Pahae Jae Sub-district, mostly still in the Growing classification, but there is still a Basic classification, and cannot be classified.